Cause Analysis and Prevention of Hole Collapse by Water Injection and Dust Removal in Qi Panjing Coal Mine. (20th October 2020) - Guo, Hua; Wang, Hai-Qiao; Chen, Shi-Qiang; Wu, Zhi-Rong
Abstract : To solve the "special coal seam" with complex coal seam structure, fault phenomenon, and many gangue layers and complex gangue lithology in Qi Panjing coal mine, the problems such as hole collapse and blockage of coal seam water injection dust removal drilling are caused. From the aspects of drilling layout, drilling technology, and gangue material consolidation, a complete set of key technologies for prevention and control of water injection and dust removal in "special coal seam, " have been formed. Seven boreholes have been drilled in I020902 return air roadway of Qi Panjing coal mine, and field comparative test has been carried out. The results show that: after adopting the complete set of key technologies of drilling prevention and control, the drilling depth is 85-100 m, the average depth is 98 m, and the drilling depth of coal seam water injection can reach 170-185 m; the footage per cycle is greatly improved, with the minimum increase of 30.86%, the maximum increase of 46.38%, and the average increase of 36.77%, to save drilling time and bring good economic benefits, and there is no collapse in the borehole hole, to ensure the safety of production. It has a good reference, and practical guiding significance for other coal mining faces, especially for "special coal seam" working face.